Prodromus of a fern flora for Bolivia. XXV. Lindsaeaceae - Smith, Alan R.; Kessler, Michael (Phytotaxa, 2017)
We provide a synopsis to the Lindsaeaceae in Bolivia, a family comprising a single genus and nine species in the country. All of the known species and varieties are widespread in South America, and many of them range into southern Mexico, Mesoamerica, and the Antilles.